2017
DOI: 10.1002/2017ja024372
|View full text |Cite
|
Sign up to set email alerts
|

Linear response of field‐aligned currents to the interplanetary electric field

Abstract: Many studies that have shown that the ionospheric, polar cap electric potentials (PCEPs) exhibit a “saturation” behavior in response to the level of the driving by the solar wind. As the magnitudes of the interplanetary magnetic field (IMF) and electric field (IEF) increase, the PCEP response is linear at low driving levels, followed with a rollover to a more constant level. While there are several different theoretical explanations for this behavior, so far, no direct observational evidence has existed to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, our prediction filters show that the filter area decreases as we limit the filter derivation to progressively higher coupling strength indicating weaker coupling or saturation. We agree with Weimer et al () that if saturation occurs, it is at a much higher value than for the polar cap potential and that a definitive answer to the question of whether FAC saturates in response to the solar wind will require additional data at higher driver strengths.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our prediction filters show that the filter area decreases as we limit the filter derivation to progressively higher coupling strength indicating weaker coupling or saturation. We agree with Weimer et al () that if saturation occurs, it is at a much higher value than for the polar cap potential and that a definitive answer to the question of whether FAC saturates in response to the solar wind will require additional data at higher driver strengths.…”
Section: Discussionsupporting
confidence: 91%
“…In one respect our results differ from previous work. A recent study by Weimer et al (2017) concludes that there is no evidence that FACs saturate with increasing interplanetary electric field. We find otherwise, although, that our saturation values are higher (~6 mV/m) than those found for the polar cap potential (3-5 mV/m).…”
Section: Discussionmentioning
confidence: 99%
“…These data are all from 1-Hz data sets from their respective missions and have had the background magnetic field removed by subtracting off the predicted geomagnetic field provided by the twelfth generation of International Geomagnetic Reference Field (IGRF) model (Thébault et al, 2015). This choice of sunward-duskward vector decomposition, as opposed to a north-east decomposition, was chosen to reduce the low-latitude numerical noise from the spherical cap harmonic analysis (SCHA) following the same reasoning as Weimer et al (2017). This creates a database of ΔB values in the sunward and duskward directions in the plane perpendicular to the magnetic field predicted by the IGRF model at each point of measurement.…”
Section: Derivation Of Fac From Bmentioning
confidence: 99%
“…It has been known that the type of the magnetospheric generator depends on the solar wind conditions. Recently, Weimer et al () found that the magnetosphere probably acts as a current source on large scale when the interplanetary electric field is large. Since the interplanetary electric field intensity has not been taken into account in the binning process, it is likely that some observations were taken when the interplanetary electric field was fairly large.…”
Section: Resultsmentioning
confidence: 99%